THE EFFECT OF FREQUENCY OF GIVING Tubifex sp TO GROWTH AND SURVIVAL OF GOURAMY LARVAE (Osphronemus gouramy, Lac) - Pratama, Yudi Anugrah; Aryani, Netti; Nuraini, Nuraini (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
AbstractGouramy (Osphronemus gouramy) is an economic freshwater fish. This study aims to effect of frequency given of Tubifex sp on growth and survival of gouramy (O. gouramy Lac) larvae. The method was an experimental method using a Completely Randomized Design (CRD) with five levels of treatment and three replications. The treatment given is the frequency of natural feeding of Tubifex sp. with the level of treatment: (P1) 1 x daily, (P2) 2 x daily, (P3) 4 x daily, (P4) 6 x daily, (P5) 8 x daily. Test fish used were 10-day-old fish larvae with stocking density of 2 fish / liter. The results showed that the frequency of given of Tubifex sp. different effect on the growth of gouramy larvae. The best results were in the treatment ofP4 with a frequency of 6 times a day at intervals of 3 hours, the result weight and length growth of 0.42g and 2.24 cm respectively, a specific growth rate of 7.80%, and a survival rate of 87.78 %.Keyword:Osphronemus gourami, Survival Rate